A cross-sectional survey on hand hygiene among nursing students working in an eastern Indian hospital. - Chattopadhyay , Saswati; Tanusri Biswas; Paramita Das; Chaudhury , Nabamita; Arindam Dasgupta; Arghya Nath; Soumi Nag (International Journal of Endorsing Health Science Research, 2023)
Background: Proper hand hygiene practices by healthcare providers are critical to prevent healthcare-associated infections (HCAIs). This study aimed to assess the hand hygiene knowledge and practices of nursing students in various departments and operation theatres of a tertiary care hospital in Eastern India. Methodology: A cross-sectional survey based on WHO questions was conducted in March-April 2022 to evaluate the hand hygiene knowledge and practices of 105 nursing students. The study included nursing students from different departments, including medicine, surgery, pediatrics, obstetrics and gynecology, eye, different ICUs (adult, NICU, and PICU), and different OTs. The collected data were analyzed according to the STROBE guidelines. Results: Of the 105 nursing students, 42.86% had no training in hand hygiene practices, highlighting the need for additional training. However, due to the COVID-19 pandemic, most students (86%) were familiar with using alcohol-based hand rubs. Most students preferred hand rubbing before giving an injection (65.74%), while hand washing was preferred after vacating a bedpan (91.42%) or being exposed to blood (89.52%). Comparing the pre-and post-workshop questionnaires showed a significant improvement in hand hygiene knowledge. However, more training is required to understand the importance of infection spread from the infected hands of HCWs. Additionally, gloves are not a substitute for hand hygiene practices, and wearing jewelry and artificial nails should be avoided. Regular training and workshops can increase awareness among nursing students. Conclusion: The findings indicate a need for ongoing training to improve hand hygiene practices among nursing students. Regular training and workshops can increase awareness and knowledge, leading to decreased incidence of HCAIs.